2013
DOI: 10.1093/infdis/jit407
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison of Dihydroartemisinin-Piperaquine and Artesunate-Amodiaquine Combined With Primaquine for Radical Treatment of Vivax Malaria in Sumatera, Indonesia

Abstract: Background. A high prevalence of chloroquine-resistant Plasmodium vivax in Indonesia has shifted first-line treatment to artemisinin-based combination therapies, combined with primaquine (PQ) for radical cure. Which combination is most effective and safe remains to be established.Methods. We conducted a prospective open-label randomized comparison of 14 days of PQ (0.25 mg base/kg) plus either artesunate-amodiaquine (AAQ + PQ) or dihydroartemisinin-piperaquine (DHP + PQ) for the treatment of uncomplicated mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…It was well tolerated with no adverse side effect on 42 days follow up. Results are similar to other trials such as comparative trial of Chloroquine and DAP in Afghanistan 16 and Open-label, randomized controlled study showing that DAP is more effective than CQ+SP, AST+SP & AL in treating uncomplicated P.Vivax malaria 16 Gametocytes were seen in 89 (86.4%) cases on enrolment, but cleared in 83(93.3%) on day 1 with 89 (100%) clearances by day 7. [Table1], similar effect of DAP was seen on gametocyte clearance in another study 17 .…”
Section: Efficacysupporting
confidence: 82%
“…It was well tolerated with no adverse side effect on 42 days follow up. Results are similar to other trials such as comparative trial of Chloroquine and DAP in Afghanistan 16 and Open-label, randomized controlled study showing that DAP is more effective than CQ+SP, AST+SP & AL in treating uncomplicated P.Vivax malaria 16 Gametocytes were seen in 89 (86.4%) cases on enrolment, but cleared in 83(93.3%) on day 1 with 89 (100%) clearances by day 7. [Table1], similar effect of DAP was seen on gametocyte clearance in another study 17 .…”
Section: Efficacysupporting
confidence: 82%
“…Its influence is illustrated by 2 trials that compared the ASAQ loose-dose combination to dihydroartemisinin–piperaquine, an ACT with a longer half-life. Lower efficacy against late recurrences of ASAQ [43] was not confirmed when PQ was coadministered [44]. This rationale is supported by the higher efficacy of CQ in preventing late recurrences compared with drugs with shorter half-lives (arthemeter–lumefantrine) in areas of low prevalence of CQR [47].…”
Section: Discussionmentioning
confidence: 99%
“…There is therefore an urgent need for novel therapeutic strategies for CRPC. Dihydroartemisinin (DHA), a semisynthetic derivative of artemisinin isolated from the Chinese medicinal plant Artemisia annua L., has been widely used as an effective antimalarial drug [15][16][17][18][19]. Recently, many studies have shown that DHA is the most potent anticancer agent among artemisinin and its derivatives [20], and has in vitro and in vivo anticancer activity in different types of human cancer cells, such as hepatocellular carcinoma, prostate cancer, gastric cancer, osteosarcoma, breast cancer, esophageal cancer, pancreatic cancer, lung cancer, and ovarian cancer [21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%